Herança da resistência do acesso de meloeiro ag-15591ghana à macrophomina phaseolina - Martins, Adriano Ferreira (Universidade Federal Rural do Semi-Árido, 2021)
Neck rot, caused by Macrophomina phaseolina (Tassi) Goid is one of the main root diseases that affect the culture in melon (Cucumis melo L.). The disease is difficult to control, as the pathogen produces resistance structures such as chlamydospores, oospores and sclerotia that remain in the soil and plant remains for several years. The use of resistant cultivars is one of the best alternatives for living with that pathogen, within a culture management program. To conduct a breeding program to obtain resistant cultivars, it is necessary to know the inheritance involved in the resistance of the donor parent. In a reaction study, the accession of melon Ag-15591Ghana was identified as resistant to Macrophomina phaseolina (Tassi) Goid. In this sense, the objective of the present work was to study the inheritance of the resistance of the referred access in crossing with the Con-Pat81Ko access. Initially, the F1 generation was obtained, from the crossing between the two parents, then the F2 generation and backcrossing (RC11) were obtained. The populations were tested for reaction to the pathogen, following the toothpick inoculation methodology. The evaluation was performed 25 days after inoculation, based on a scale of severity scores ranging from 0 to 5, where 0: Asymptomatic and 5: More than 50% of infected tissues. Genetic models were tested using maximum likelihood in mixtures of normal density functions. Based on the likelihood functions for each model, it was possible to compose tests of interest, considering different hypotheses. The results showed that the inheritance of Ag-15591Ghana access resistance is controlled by a larger gene with the presence of an additive and dominance effect
Keywords: Cucumis melo L.; Manejo; Doenças radiculares; Controle; Cucumis melo L.; Management; Root diseases; Control; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA